Correlates of values of teachers of selected public and private schools in Metro Manila implications for administration - Sindico, Evelyn Solo 1944- (1988)
Stepwise discriminant analysis was used to measure the values of 505 public and private school teachers from 37 elementary schools related to the dignity and worth of the individual, education, integrity, freedom, social justice and common good, family unity, marriage and sex, work, and faith in God. Findings reveal divergence in philosophical orientation. Teachers have predominantly Christian orientation on dignity, freedom, family unity, marriage and sex. Majority are still Christian in orientation on social justice and common good but almost half are modern. Teachers have modern orientation on education, integrity, work and faith in God. Teachers' values are related to sex, age, family size, civil and marital status, education of father and mother, marital status of parents, occupation of father, family income, educational attainment and work experience of respondents. Correlates of teachers' values show a strong tendency towards modernism.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Values; Moral education